Hydrogeological conceptual site models data analysis and visualization - Kresic, Neven; Mikszewski, Alex. (Boca Raton, FL CRC Press, 2013)
"From their origins, exploration and inquiry in the earth sciences have been dependent on conceptual models and data visualizations to test theories and convey findings to the general public. One can appreciate the power and importance of conceptual graphics by flipping through the pages of a National Geographic magazine. Data visualization is inextricably linked to quantitative spatial data analysis - the two major forms of which, for the earth sciences, are statistical interpolation and modeling"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Groundwater; Hydrology -- Methodology